2019
DOI: 10.1002/adma.201806701
|View full text |Cite
|
Sign up to set email alerts
|

Precisely Defined Conjugated Oligoelectrolytes for Biosensing and Therapeutics

Abstract: Conjugated oligoelectrolytes (COEs) are a relatively new class of synthetic organic molecules with, as of yet, untapped potential for use in organic optoelectronic devices and bioelectronics systems. COEs also offer a novel molecular approach to biosensing, bioimaging, and disease therapy. Substantial progress has been made in the past decade at the intersection of chemistry, materials science and the biological sciences developing COEs and their polymer analogues, namely conjugated polyelectrolytes (CPEs), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 195 publications
(214 reference statements)
0
65
0
1
Order By: Relevance
“…These studies have demonstrated that effective and reversible photomodulation can be achieved both in vitro and in vivo, by the covalent binding of the azobenzene unit to the selected target. Alternatively, one can exploit non‐covalent interactions to assist the incorporation of photoactive molecules in bio‐systems 26–30. Although this method is less specific than the covalent approach, the relatively weak non‐covalent interactions still allow for driving affinity to various bio‐interfaces, while ensuring full reversibility and much lower invasiveness.…”
Section: Figurementioning
confidence: 99%
“…These studies have demonstrated that effective and reversible photomodulation can be achieved both in vitro and in vivo, by the covalent binding of the azobenzene unit to the selected target. Alternatively, one can exploit non‐covalent interactions to assist the incorporation of photoactive molecules in bio‐systems 26–30. Although this method is less specific than the covalent approach, the relatively weak non‐covalent interactions still allow for driving affinity to various bio‐interfaces, while ensuring full reversibility and much lower invasiveness.…”
Section: Figurementioning
confidence: 99%
“…These conformational‐dependent optical characteristics make LCOs promising biorecognition element for the selective and sensitive detection of biomacromolecules. [ 152 ]…”
Section: Optotracing By Luminescent‐conjugated Oligothiophenesmentioning
confidence: 99%
“…Recently, cationic conjugated oligomers (including cationic oligo(p-phenylene vinylene), oligo(p-phenylene ethynylene)s, and oligo-(thiophene ethynylene) (OTE)), exhibit high antibacterial and antitumor activity on account of their noticeable PDT effect. [30][31][32] In addition, cationic conjugated oligomers are usually featured with strong light-harvesting ability and high fluorescence quantum yield, 33,34 which forms the solid base for investigating the dynamic distribution of drugs inside cells. 35 Particularly, OTE can physically break the membrane structure of microorganism efficiently.…”
Section: Introductionmentioning
confidence: 99%